Historical and projected HFC-410A emission from room air conditioning sector in China. (1st September 2019) - Liu, Lisha; Dou, Yanwei; Yao, Bo; Bie, Pengju; Wang, Lei; Peng, Min; Hu, Jianxin
Abstract: China's room air conditioning (RAC) sector is now undergoing a substitution of HCFC-22 (CHClF2 ) by HFC-410A (a blend of HFC-125 (C2 HF5 ) and HFC-32 (CH2 F2 )) as refrigerant. However, HFC-410A is also one of the strong greenhouse gases (GHGs) and will be regulated under the Kigali Amendment to the Montreal Protocol. In this study, an updated HFC-410A emission inventory for China's RAC sector is established for the period of 2006–2017 with a projection to 2050 based on a bottom-up method. Our estimation indicates that the HFC-410A emissions increased from 0.0092 Gg yr −1 to 12.0 Gg yr −1 with an annual increase of 115.7%/yr during 2006–2017. More than 95% of the emissions were from end-of-life process. Under a business-as-usual (BAU) scenario, projected emissions will continuously grow to 89.2 (54.8–126.0) Gg yr −1 in 2050. However, under a mitigation scenario with implementation of the Kigali Amendment, emissions will peak at 63.8 Gg yr −1 in 2039 and then decline to 43.1 (26.1–62.0) Gg yr −1 in 2050, and about 373 Gg of cumulative emission could be curbed during 2018–2050. Additionally, we find that the Beijing-Tianjin-Hebei region, the Yangzi River Delta, the Pearl River Delta and provincial capital cities show greater HFC-410A emission intensities per unit of area than those of the rest of China during 2009–2017. Graphical abstract: Image 1 Highlights: Updated emission factors from filed survey are applied to estimate HFC-410A emission from RAC in China. HFC-410A emission exhibited a tremendous growth rate from 2006 to 2017 in China. HFC-410A emission is projected to 2050 under BAU and mitigation scenarios. City level HFC-410A emission intensity is reported.